Long-axis fractional shortening and mitral annulus motion in dogs - Sousa, Marlos Gonçalves; Gava, Fabio Nelson [UNESP]; Da Silva Filho, Jorge Cardoso [UNESP]; Da Silva, Sheila Nogueira Saraiva [UNESP]; Camacho, Rafael Rodrigues [UNESP]; Carareto, Roberta; Wolf, Marcela; Camacho, Aparecido Antonio [UNESP] (Universidade Estadual de Londrina, 2016)
Ventricular systolic dynamics involves the contraction of transverse and longitudinal myocardial fibers. Unfortunately, only the activity of the transverse myocardial fibers is foreseen by the standard systolic echocardiographic parameters. Although strain and strain rate have been used to assess the radial, circumferential and longitudinal planes of cardiac contraction, such analysis requires advanced equipment which is not always available in veterinary medicine. On the contrary, some unusual parameters may be recorded via standard methodology, allowing for the specific evaluation of left ventricular longitudinal contractility. In this study, the longitudinal contractile activity was evaluated using the long-axis fractional shortening and the mitral annulus motion, which were compared with several standard echocardiographic parameters in 14 beagles, including seven with asymptomatic mitral valve disease. The long-axis fractional shortening was positively correlated with both the mitral annulus motion and the end-diastolic left-ventricular diameter. Also, a significant correlation was found to exist between the mitral annulus motion and the left-ventricular end-diastolic diameter, which is likely supportive of its preload dependency. Even though no difference was documented in either mitral annulus motion or long-axis fractional shortening between healthy dogs and dogs with mitral valve disease, the latter only included animals with minimal cardiac remodeling, with no overt compromise of systolic function. Since it is possible to obtain these two parameters with any echocardiographic equipment, their inclusion in the routine exam would probably add information regarding the activity of the longitudinal myocardial fibers, whose functional deterioration supposedly occurs prior to the impairment of transverse fibers.
Keywords: Echocardiogram; Endocardiosis; Left ventricle; Longitudinal contractility; Systolic function